(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
There is no doubt that phraseological units of all types are “dead” in collections and dictionaries. In fact, most of them do not include any contexts and ignore diachronic considerations. Thus in Uzbek language there are only a few dictionaries devoted to phrases. That is not to say that individual investigations of the contextualised use of proverbs, proverbial expressions, and other phrases do not exist.